2016
DOI: 10.1186/s12958-016-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet-rich plasma in a model of bovine endometrial inflammation in vitro

Abstract: BackgroundEndometritis reduces fertility and is responsible for major economic losses in beef and dairy industries. The aim of this study was to evaluate an alternative therapy using platelet-rich plasma (PRP). PRP was tested in vivo, after bovine intrauterine administration, and in vitro on endometrial cells.MethodsBovine endometrial cells were cultured until passage (P) 10 with 5 % or 10 % PRP. Effect of PRP on endometrial cell proliferation and on the expression of genes [prostaglandin-endoperoxide synthase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 63 publications
1
57
1
Order By: Relevance
“…The underlying mechanisms through which PRP acts as a modulator alleviating inflammation are further strengthened by in vitro studies of PRP treatment on animal models (20,45). Proliferation as well as gene expression of endometrial cells have already been demonstrated and confirmed by in vitro bovine studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The underlying mechanisms through which PRP acts as a modulator alleviating inflammation are further strengthened by in vitro studies of PRP treatment on animal models (20,45). Proliferation as well as gene expression of endometrial cells have already been demonstrated and confirmed by in vitro bovine studies.…”
Section: Discussionmentioning
confidence: 93%
“…c-MYC is involved in cell in vivo 33: 515-521 (2019) proliferation and growth, and is activated by EGF, a component of PRP. This is one representative of many examples of the effects of PRP, demonstrating its effectiveness in reducing gene expression of pro-inflammatory factors such as interleukin 1β, interleukin 8, prostaglandin-endoperoxide synthase 2, and inducible nitric oxide synthetase, revealing its promising prospectives in in vivo regenerative therapy in endometritis (45). El-Sharkawy et al reported that treatment with PRP increased the release of various growth factors such as insulin-like growth factor-I, fibroblast growth factor, epidermal growth factor and transforming factor β (46).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are also cytokines such as IL-1, IL-8 in PRP 50 . Marini et al showed that PRP reduced IL-1B and IL-8 release in endometrial tissues and they attributed the anti-inflammatory effect of PRP to this reduction 51 . Some of the cytokines held responsible for the pathophysiology, which are shown to increase in the peritoneal fluid in endometriosis, are IL-1 and IL-8 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that cell proliferation and tissue growth depend not only on single growth factors, but on an overall favorable environment, another possible explanation on the mode of action of PRP on endometrial growth and receptivity is via its anti-microbial, anti-inflammatory properties, as demonstrated on human chondrocytes [19] and on equine and bovine uterine infections [20][21][22][23]. In humans, chronic endometritis (CE) has a high prevalence among infertile patients (range 2.8 to 46%) [24,25].…”
Section: Prp and Human Reproductionmentioning
confidence: 99%